Learning through Reflection After Nursing Practice Training for People with Mental Health Problems of Nursing Students - เวียงเพิ่ม สมจิตต์; แสงสาย วัชรี; บารมี แสงนภา; เสาะสืบ ภาวินี (Journal of Health Science of Thailand, 2020)
Clinical teaching management is considered a key to nursing education management aiming at developing learners’ skill and competency in nursing practice and cognitive skills, as well as in situation-based problem-solving during their work. Applying reflection to clinical teaching management helps nursing students to learn regarding what they did, its consequences, and perspectives to solve the problems. The qualitative research aimed to understand perception and experience among the third-year nursing students regarding learning through reflection after nursing practice training on the subject of Nursing Care of Person with Mental Health Problems Practicum. The participants were 40 nursing students. Data were collected by using written diary of reflection between March and April 2018. Content analysis was used to analyze the data. The results of the study illustrated three main concepts follows: 1) the learning experience consist of group therapy, psychiatric history- taking, communication mental health and therapeutic relationship; 2) Interpersonal relationships consist interdisciplinary relationships and patient relationships; and 3) emotional experience consist of anxiety and worried during initial phase of therapeutic relationship. The result of the study showed that interaction with each other, help to facilitate in students’ reflective process. Nursing students’ reflection during clinical practice is effective learning in personal and professional level. Therefore, nursing instructors should help to promote the reflection behavior of nursing students while clinical practice. This will help nursing students learn to become high standards of professionalism in their work.